UDC: 8 1751, The Role of Etymology In Vocabulary Acquisition - Zafarovich, Axundjonov (Innovative Technologica: Methodical Research Journal, 2025)
Vocabulary acquisition is widely recognized as one of the most challenging aspects of second language learning. While numerous approaches to vocabulary instruction exist, the potential of etymology—studying the origin and evolution of words - remains underexplored in language pedagogy. This article examines the role of etymology in enhancing vocabulary acquisition, emphasizing its cognitive, pedagogical, and metacognitive benefits. It argues that integrating etymology into language learning strategies fosters not only deeper semantic understanding but also broader cognitive engagement, facilitating word retention and expanding linguistic competence. Drawing on theoretical frameworks and empirical research, this study highlights the potential of etymology to significantly improve language learners’ lexical depth and intercultural awareness.